Evaluation of Nutrition Awareness of Rural Women Concerning Cardiovascular Disease: Nutrition Awareness of Rural Women Concerning Cardiovascular Disease - Saeed, Anam; Khan, Mahnaz Nasir; Saeed, Soda (Pakistan Journal of Health Sciences, 2025)
Cardiovascular disease is the leading component of non-communicable diseases. Atherosclerotic and hypertensive diseases, mostly ischemic heart disease and stroke together with heart failure are the main Cardiovascular disease entities and signify threats to population health. In Pakistan, the incidence of Cardiovascular disease is more common among female as compared to male. The ratio of male to female patients is 1:3. Nutrition plays a significant role in the development and prevention of heart diseases. Objective: To evaluate of Nutrition Awareness of Rural Women Concerning Cardiovascular Disease. Methods: A descriptive cross-sectional study was carried out to assess the nutritional knowledge and health-related behaviour regarding cardiovascular disease of rural women aged 35 to 45. The research was a survey based with a well-established interview-based questionnaire was used to collect data. The sample was selected using random sampling and comprised of 300 respondents. Results: The results revealed rural women had little knowledge regarding good nutrition practices like consumption of high fat, low fiber, high amount of red meat, full-fat milk, and low amount of fruits and vegetables can lead to heart disease. Conclusions: It was concluded that assessment of nutritional knowledge regarding Cardiovascular disease of rural women age 35 to 45 gave statistical evidence of increasing risk factors for heart diseases. Results were useful in the development of gender-specific messages to increase awareness about heart disease and to promote lifestyle behaviours to decrease risk.